PERBANDINGAN KARAKTERISTIK LINGKUNGAN SOSIAL SEKOLAH DAN KESEHATAN MENTAL ANAK USIA SEKOLAH - Nurjannah, Siti; Nauli, Fathra Annis; Karim, Darwin (Jurnal Keperawatan Profesional, 2023)
The social environment of the school plays an important role in the development of           students' mental health. This study aims to compare     the characteristics of the school's social environment             and the mental health of school-age children at SD   ANNUR Pekanbaru and SDN 166 Pekanbaru. Methods: The design used in this research is descriptive comparative with a sample of 74 respondents using simple random sampling. This study used a modified researcher questionnaire             regarding the characteristics of the school's social     environment and the Strength and Difficulties Questionnaire. Results: The results showed that the majority of respondents were female as many as 41 students (55.4%) aged 10 years as many as 47 students(63.5%), and the majority lived with their     parents as many as 65 students (87.8%) with the       status of parents with 61 students (82.4%). Comparison of the variables characteristic of the       school's social environment and the mental health of         school-age children shows that the majority of student-teacher relationships are good, namely             52.6%, the majority of student-student relationships             are good, namely 51.4%, the majority of student-teacher relationships are good, namely as much as 59.5%, and the majority of the mental health of          school-age children is normal, namely as much as 56.8%.Conclusion: A conducive school social environment will lead to good mental health of students, and vice versa. It is hoped that the results of         this study can be used to improve the characteristics             of a better school social environment so that the mental health of school-age children can also be good.